2014
DOI: 10.1111/pce.12375
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modulation of the energy sensor Snf1‐related protein kinase 1 on hypoxia adaptation and salt stress tolerance in Arabidopsis thaliana

Abstract: Terrestrial plants are exposed to complex stresses of high salt-induced abscisic acid (ABA) and submergence-induced hypoxia when seawater floods fields. Many studies have investigated plant responses to individual stress conditions, but not so much for coupled or sequentially imposed stresses. We examined molecular regulatory mechanisms of gene expression underlying the cellular responses involved in crosstalk between salt and hypoxia stresses. Salt/ABA- and AtMYC2-dependent induction of a synthetic ABA-respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…Under osmotic stress conditions, ABA also controls the activity of the starch amylases BAM1 and AMY3 in leaves through the AREB/ ABF-SnRK2 kinase signaling pathway (Thalmann et al, 2016). Moreover, SnRK1 also has been identified as regulator of the MYC2 TF in the regulation of ABA-responsive elements (Im et al, 2014), and a further functional link between SnRK1 and ABA signaling was provided in a study of Suc responses in apple (Malus domestica), where the overexpression of the C2 domain ABA Insensitive Protein1 (MdCAIP1) was found to cause insensitivity toward ABA (Liu et al, 2017b). This phenotype was abolished in the presence of active MdSnRK1, which was shown to directly phosphorylate MdCAIP1 and thereby render it a target for 26S proteasomal degradation.…”
Section: Snrk1 In Metabolic and Hormone Signaling Under Stress Conditmentioning
confidence: 99%
See 2 more Smart Citations
“…Under osmotic stress conditions, ABA also controls the activity of the starch amylases BAM1 and AMY3 in leaves through the AREB/ ABF-SnRK2 kinase signaling pathway (Thalmann et al, 2016). Moreover, SnRK1 also has been identified as regulator of the MYC2 TF in the regulation of ABA-responsive elements (Im et al, 2014), and a further functional link between SnRK1 and ABA signaling was provided in a study of Suc responses in apple (Malus domestica), where the overexpression of the C2 domain ABA Insensitive Protein1 (MdCAIP1) was found to cause insensitivity toward ABA (Liu et al, 2017b). This phenotype was abolished in the presence of active MdSnRK1, which was shown to directly phosphorylate MdCAIP1 and thereby render it a target for 26S proteasomal degradation.…”
Section: Snrk1 In Metabolic and Hormone Signaling Under Stress Conditmentioning
confidence: 99%
“…In a previous study, it was shown that AKIN10 overexpression resulted in decreased MYC2 protein levels, which could be counteracted by addition of proteasome inhibitor MG132. The authors demonstrated that AKIN10 and MYC2 physically interact, and identified the Ser that when phosphorylated is crucial for proteasomal degradation of MYC2 (Im et al, 2014).…”
Section: Snrk1 In Metabolic and Hormone Signaling Under Stress Conditmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein blot analysis followed a previously described method (Im et al 2014). The protoplast samples were incubated and collected, and then mixed with 59 sodium dodecyl sulfate (SDS) sample buffer.…”
Section: Protein Blot Analysismentioning
confidence: 99%
“…Saltwater increase the concentration of Na + and Cl -in plant tissues, altering ionic ratios in plants and producing ion toxicity (Barrett-Lennard and Shabala, 2013;Grattan and Grieve, 1998;Rhoades et al, 1999). As a result, saltwater can have a negative impact on growth, compromising plant development and survival (Barrett-Lennard and Shabala, 2013;Im et al, 2014) Stolon connections allow clonal plants to be physiologically integrated (i.e. to shareresources between connected modules).…”
Section: Introductionmentioning
confidence: 99%